2000
DOI: 10.1161/01.str.31.2.463
|View full text |Cite
|
Sign up to set email alerts
|

Which Parameters of Beat-to-Beat Blood Pressure and Variability Best Predict Early Outcome After Acute Ischemic Stroke?

Abstract: Background and Purpose-In hypertensive populations, increasing blood pressure (BP) levels and BP variability (BPV) are associated with a greater incidence of target organ damage. After stroke, elevated 24-hour BP levels predict a poor outcome, although it is uncertain whether shorter-length BP recordings assessing mean BP levels and BPV have a similar predictive role. The objectives of this study were to compare the different measures of beat-to-beat BP and BPV on outcome after acute ischemic stroke and asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(122 citation statements)
references
References 63 publications
(59 reference statements)
7
113
0
2
Order By: Relevance
“…There were fewer data for combined death or dependency (1290, 11.8%) and combined death or deterioration (1196, 11.0%). These outcomes were assessed with validated stroke scales in 7 articles (Rankin score, [27][28][29][30][31] Scandinavian Neurological Stroke Scale, 30,32 Canadian Neurological Score, 33 or National Institutes of Health Scale 29 ). The other studies used either nonvalidated scales 9 or qualitative assessments, such as discharge disposition.…”
Section: Resultsmentioning
confidence: 99%
“…There were fewer data for combined death or dependency (1290, 11.8%) and combined death or deterioration (1196, 11.0%). These outcomes were assessed with validated stroke scales in 7 articles (Rankin score, [27][28][29][30][31] Scandinavian Neurological Stroke Scale, 30,32 Canadian Neurological Score, 33 or National Institutes of Health Scale 29 ). The other studies used either nonvalidated scales 9 or qualitative assessments, such as discharge disposition.…”
Section: Resultsmentioning
confidence: 99%
“…19 This underscores the limitation of studies that have addressed the value of single measurements of BP after stroke in predicting outcome. Our analysis, however, could rely on repeated BP measurements at fixed intervals and was able to consider the effects of both a longer course of BP (weighted average MAP) and BP fluctuations (a 30% increase and decrease from baseline MAP).…”
Section: Discussionmentioning
confidence: 99%
“…6 Most studies have found that high 24-hour BP variability is associated with organ damage and may contribute to cardiovascular risk prediction, over and beyond mean BP. [7][8][9][10][11][12][13][14][15][16][17] However, the degree to which variability improves the prediction of cardiovascular risk is controversial. [18][19][20] Previous studies have shown that nighttime BP is generally a better predictor of cardiovascular outcomes than daytime BP in patients with hypertension, and diminished nocturnal decline in BP is associated with or predictive of organ damage and cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%